Comprehending toll-like receptors: pivotal element in the pathogenesis of sepsis and its complications - Wei Wang; Shengtian Mu; Dongli Yan; Huan Qin; Zhen Zheng (Frontiers in Immunology)
Sepsis, a critical systemic inflammatory response syndrome elicited by pathogenic microorganisms, poses a significant challenge in clinical practice due to its rapid progression and potential for multi-organ failure. This review delineates the intricate roles of Toll-like receptors (TLRs), essential components of the innate immune system, in mediating host responses during sepsis. TLRs recognize pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), thereby initiating signaling cascades that lead to the synthesis of pro-inflammatory cytokines and chemokines. However, the dysregulation of TLR signaling can precipitate a hyper-inflammatory state known as a “cytokine storm,” characterized by excessive tissue damage and complications such as Acute Respiratory Distress Syndrome (ARDS) and acute kidney injury (AKI). Several therapeutic strategies targeting TLR pathways are under exploration to mitigate the adverse effects of sepsis. Despite advancements, significant gaps remain, including the need for robust clinical validation and understanding of TLR expression variability among individuals. Future research should focus on elucidating the precise molecular mechanisms governing TLR-mediated responses and developing human-specific therapeutic interventions. This review aims to consolidate current knowledge on TLRs in sepsis, highlighting their dual roles as both defenders against infection and contributors to pathological conditions, thereby informing future therapeutic strategies.